Fast disintegrating crystalline solid dispersions of simvastatin for incorporation into orodispersible tablets - Pabari, Ritesh M; Jamil, Asha; Kelly, John G; Ramtoola, Zebunnissa (International Journal of Pharmaceutical Investigation)
Aim: Spray dried solid dispersion (SDP) of crystalline simvastatin (SIM) in a fast disintegrating matrix of superdisintegrants was studied as a method to enhance SIM dispersibility, rheology, compactibility and compressibility for incorporation into orodispersible tablets (ODTs). Materials and Methods: The superdisintegrants investigated were crospovidone (CP), sodium starch glycollate (SSG) and calcium silicate (CS) were spray dried with simvastatin to form SDPs. Results: The SDPs were characterized and the median particle size of SDPs was similar or greater than the SIM, contributing to good rheology of SDPs, while the low bulk density of SDPs indicated a high compactibility. Interestingly electron micrographs for SDPs showed a CP or CS carrier coating of the SIM crystals, contributing to its rheology. Thermal analysis and X-ray diffraction confi rmed that SIM was crystalline in the SDPs and no interaction between SIM and any of the carrier(s) was shown by Fourier transform-infra red. Drug content analysis showed a SIM content of 90-95% in SDPs containing CP or CS, while a higher SIM content of 143% was found in SDP containing SSG. When formulated as ODTs, blend containing SIM SDPs in CP showed ease of tableting, regardless of the turret speed. In comparison, tablet blend consisting of a physical mix (PM) of SIM and CP could only be tableted at the lower turret speed of 7 rpm. ODTs formulated using SIM SDPs in CP showed a higher extent of dissolution, compared to the ODTs containing corresponding PM or the commercially available SIM Zocor® tablets (ANOVA, P < 0.05). Conclusion: SDP using disintegrants as carriers may offer an alternative formulation approach for ODTs of poorly soluble drugs.
Keywords: Crystallinity; orodispersible tablets; simvastatin; solid dispersion; spray drying; superdisintegrants